Proto-neutron star evolution with improved charged-current neutrino–nucleon interactions. Issue 1 (8th January 2022) - Pascal, A; Novak, J; Oertel, M
ABSTRACT: We perform simulations of the Kelvin–Helmholtz cooling phase of proto-neutron stars with a new numerical code in spherical symmetry and using the quasi-static approximation. We use for the first time the full set of charged-current neutrino–nucleon reactions, including neutron decay and modified Urca processes, together with the energy-dependent numerical representation for the inclusion of nuclear correlations with random phase approximation. Moreover, convective motions are taken into account within the mixing length theory. As we vary the assumptions for computing neutrino–nucleon reaction rates, we show that the dominant effect on the cooling time-scale, neutrino signal, and composition of the neutrino-driven wind comes from the inclusion of convective motion. Computation of nuclear correlations within the random phase approximation, as compared to mean field approach, has a relatively small impact.